2017
DOI: 10.1055/s-0037-1606628
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of Two Barbed Suture Configurations for Flexor Tendon Repair

Abstract: The current study compares the strength of a previously studied technique for flexor tendon repair with barbed sutures to an experimental approach that aligns all the barbs to oppose distraction. Twelve flexor tendons from cadaveric specimens were mechanically tested following repair of simulated zone II tendon injuries. Two repair techniques utilizing barbed sutures were studied: the Marrero-Amadeo four-core barbed suture approach and the experimental configuration with all barbs on four cores opposing distra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Regardless of the suture material and technique, the most common mode of failure in our study was suture pull-out. Previous studies have demonstrated that traditional repairs failed mostly by suture rupture, whereas barbed suture repairs most commonly failed by either suture pull-out or breakage 3 7 11 , 14 16 . The discrepancy in the mode of failure between our study and previous reports may be due to differences in the tendon model that was used and the suture purchase length for repairs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regardless of the suture material and technique, the most common mode of failure in our study was suture pull-out. Previous studies have demonstrated that traditional repairs failed mostly by suture rupture, whereas barbed suture repairs most commonly failed by either suture pull-out or breakage 3 7 11 , 14 16 . The discrepancy in the mode of failure between our study and previous reports may be due to differences in the tendon model that was used and the suture purchase length for repairs.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in suture materials reintroduced the possibility of using barbed sutures for tendon repairs. The advantages of barbed tenorrhaphy are minimal bulk and lower gliding resistance due to the knotless design, better load distribution along the entire suture length caused by the barbs locking into the tendon, and improved tendon flow resulting from the reduction of constricting forces [1,3,5]. Furthermore, the barbed suture technique is quicker than other techniques, and is easy to perform and less demanding in terms of surgical skills.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations